N6-Methyladenosine Modification of LncRNA DUXAP9 Promotes Renal Cancer Cells Proliferation and Motility by Activating the PI3K/AKT Signaling Pathway - Tan, Lei; Tang, Yiming; Li, Hongbo; Li, Pengju; Ye, Yunlin; Cen, Junjie; Gui, Chengpeng; Luo, Junhang; Cao, Jiazheng; Wei, Jinhuan (Frontiers in Oncology, 2021)
Most localised human renal clear cell carcinoma (ccRCC)-related deaths result from cancer recurrence and metastasis. However, the precise molecular mechanisms largely remain unknown. In recent years, an increasing number of long noncoding RNAs (lncRNAs) have been shown to be vital regulators of tumorigenesis. In this study, we characterized a lncRNA DUXAP9 and the upregulation of DUXAP9 was analyzed by quantitative real-time PCR in 112 pairs of localised ccRCC tumor tissues compared with adjacent normal tissues. Kaplan–Meier curves showed that patients of localised ccRCC with high DUXAP9 expression had poorer overall survival (P<0.01) and progression-free survival (P<0.05) than cases with low DUXAP9 expression. Multivariate Cox regression analysis also showed that high DUXAP9 expression was an independent risk factor for poor prognosis in localised ccRCC (p<0.05). DUXAP9 knockdown in renal cancer cells inhibited renal cancer cells proliferation and motility capacities in vitro and reversed epithelial–mesenchymal transition (EMT), whereas overexpression of DUXAP9 promoted renal cancer cells proliferation and motility capacities in vitro and induced EMT. Pull-down, RNA immunoprecipitation and RNA stability assays (involving actinomycin D) showed that DUXAP9 was methylated at N6-adenosine and binds to IGF2BP2, which increases its stability. DUXAP9 activate PI3K/AKT pathway and Snail expression in renal cancer cells. DUXAP9 may be useful as a prognostic marker and/or therapeutic target in localised ccRCC.